PENGEMBANGAN STRATEGI PEMASARAN MENINGKATKAN MINAT BERBELANJA DI PASAR BERSIH BEKASI - Wuryan, Sophiyanto; Baskara, Ika; Wahyudi, Endik (JURNAL LENTERA BISNIS, 2026)
This study aims to examine the effects of product, price, and service quality on consumers’ shopping interest at Pasar Bersih Telaga Mas, North Bekasi, while also formulating marketing strategies that reflect actual field conditions. A quantitative approach was employed, with data collected through questionnaires administered to 60 respondents. The data were analyzed using multiple linear regression to assess both partial and simultaneous relationships among variables. The findings indicate that product and price have a positive and statistically significant effect on consumers’ shopping interest, with product emerging as the most dominant variable. In contrast, service quality does not exhibit a significant effect. Simultaneously, all three variables significantly influence shopping interest, as reflected in a high coefficient of determination, indicating that the model accounts for a substantial proportion of the variation in consumer interest. These results suggest that improving product quality and variety, along with maintaining competitive and consistent pricing, constitutes the primary basis for enhancing consumer interest. The study is expected to provide practical considerations for market management in formulating more targeted and contextually grounded marketing policies and strategies.